Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Thảo Bùi

Rút gọn biểu thức B= căn (x^2-4x+4) - căn (x^2+4x+4)

Hoàng Lê Bảo Ngọc
31 tháng 5 2016 lúc 11:31

\(\sqrt{x^2-4x+4}-\sqrt{x^2+4x+4}=\sqrt{\left(x-2\right)^2}-\sqrt{\left(x+2\right)^2}=\left|x-2\right|-\left|x+2\right|\)

1. Với \(x\ge2\)thì : 

\(B=\left(x-2\right)-\left(x+2\right)=x-2-x-2=-4\)

2. Với \(x\le-2\)thì : 

\(B=\left(2-x\right)-\left(-x-2\right)=2-x+x+2=4\)

3. Với \(-2< x< 2\)thì 

\(\left(2-x\right)-\left(x+2\right)=2-x-x-2=-2x\)


Các câu hỏi tương tự
Thủy Thu-
Xem chi tiết
Nguyễn Hồng Thắm
Xem chi tiết
trần thị kim thư
Xem chi tiết
Nguyễn Đoan Hạnh Vân
Xem chi tiết
Thảo Bùi
Xem chi tiết
bảo anh trần
Xem chi tiết
Sang Trần Tiến
Xem chi tiết
Gia Bảo
Xem chi tiết
Incredient
Xem chi tiết